2023
DOI: 10.1007/s44228-023-00041-x
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax: A New Partner in the Novel Treatment Era for Acute Myeloid Leukemia and Myelodysplastic Syndrome

Abstract: Background Acute Myeloid Leukemia (AML) and Myelodysplastic Syndrome (MDS) are two closely related blood cancers that are more frequent in older adults. AML is the most common type of adult acute leukemia, and MDS is characterized by ineffective blood cell production and abnormalities in the bone marrow and blood. Both can be resistant to treatment, often due to dysfunction in the process of apoptosis, the body’s natural mechanism for cell death. Venetoclax, an orally-administered medication that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…As a consequence, free Bim can activate Bak/Bax on the surface of mitochondria, inducing PTP opening and the death of cancer cells [ 87 , 88 , 89 ]. Preclinical studies demonstrated that these inhibitors were able to inhibit tumor growth in vivo and in vitro; however, clinical studies are needed to prove their real efficacy [ 90 ].…”
Section: Molecules Targeting Mitochondrial Homeostasismentioning
confidence: 99%
“…As a consequence, free Bim can activate Bak/Bax on the surface of mitochondria, inducing PTP opening and the death of cancer cells [ 87 , 88 , 89 ]. Preclinical studies demonstrated that these inhibitors were able to inhibit tumor growth in vivo and in vitro; however, clinical studies are needed to prove their real efficacy [ 90 ].…”
Section: Molecules Targeting Mitochondrial Homeostasismentioning
confidence: 99%
“…The Bcl2-inhibitor venetoclax is used in the treatment of various malignancies, including AML, and various lymphoid malignancies [103][104][105][106][107][108][109]. A recent study identified CK2 as a major regulator of resistance to venetoclax in mantle cell lymphoma; additional experimental studies have demonstrated that even though the CK2 inhibitor CX-4945/silmitasertib alone does not affect the viability of mantle cell lymphoma cell lines or primary samples, CK2 inhibition strongly synergizes with the antilymphoma effects of venetoclax and the Bruton's tyrosine kinase inhibitor ibrutinib [106][107][108].…”
Section: Combination Of Pk2 Inhibition and The Bcl2 Inhibitor Venetoc...mentioning
confidence: 99%
“…Venetoclax has direct antileukemic effects on AML cells and is now used in the treatment of AML [103][104][105] and mantle cell lymphoma [106][107][108][109], and MSCs support the proliferation and survival of both AML cells and mantle cell lymphoma cells [92,93,[106][107][108][109][110]. Furthermore, CK2 inhibition causes a similar modulation of intracellular proapoptotic signaling including Mcl1 reduction in AML cells and mantle cell lymphoma cells [61,65,[106][107][108][109].…”
Section: Combination Of Pk2 Inhibition and The Bcl2 Inhibitor Venetoc...mentioning
confidence: 99%
“…BCL-2 is an antiapoptotic protein that is overexpressed in AML cells and promotes leukemic blast survival through regulation of the mitochondrial apoptotic pathway . Venetoclax (VEN), a highly selective BCL-2 inhibitor, in combination with hypomethylating agents or low-dose cytarabine has been approved as a standard option for newly diagnosed AML patients who are unfit for intensive chemotherapy. Recent studies have indicated the synergistic effect of VEN in combination with FLT3 inhibitors in FLT3-ITD AML models, , likely due to the simultaneous downregulation of MCL-1 and BCL-XL antiapoptotic proteins, which can facilitate VEN resistance. , Moreover, early phase clinical trials have shown encouraging response rates and survival benefits in FLT3 mutant AML patients after combination therapy with VEN and FLT3 inhibitors. Nevertheless, this combination is associated with poor bioavailability, dose-dependent myelosuppression, overlapping systemic toxicity, and drug resistance, limiting its clinical benefits.…”
Section: Introductionmentioning
confidence: 99%